Aerosols Produced by Upper Gastrointestinal Endoscopy: A Quantitative Evaluation. (19th January 2021) - Sagami, Ryota; Nishikiori, Hidefumi; Sato, Takao; Tsuji, Hiroaki; Ono, Masami; Togo, Kazumi; Fukuda, Kensuke; Okamoto, Kazuhisa; Ogawa, Ryo; Mizukami, Kazuhiro; Okimoto, Tadayoshi; Kodama, Masaaki; et al.
Abstract : INTRODUCTION: During the coronavirus disease 2019 pandemic, whether endoscopy generates aerosols needs to be determined. METHODS: In patients undergoing upper gastrointestinal endoscopy with an enclosure covering their heads, 0.3–10-μm aerosols were measured for 60 seconds before, during, and after endoscopy by an optical counter. Whether aerosols increased in the situation with and without endoscopy was examined. RESULTS: The analysis included 103 consecutive patients undergoing endoscopy and 90 control patients. Aerosols increased significantly during endoscopy compared with the control group. Body mass index and burping were significant factors related to increased aerosols during endoscopy. DISCUSSION: Upper gastrointestinal endoscopy was an aerosol-generating procedure.